1994
DOI: 10.1111/j.1467-8624.1994.tb00766.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of School Transitions in Early Adolescence on the Self-System and Perceived Social Context of Poor Urban Youth

Abstract: This study examined the effects of the normative school transition (n= 580) during early adolescence on the self‐system and perceived school and peer social contexts of poor, black (n= 161), white (n= 146), and Latino (n= 273) youth in the public school systems of 3 eastern urban cities. The results revealed negative effects of the school transition on the affective and behavioral domains of the self‐system. These declines in self‐esteem, class preparation, and grade‐point average (GPA) were common across race… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
162
5
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(190 citation statements)
references
References 30 publications
21
162
5
2
Order By: Relevance
“…However, other longitudinal studies in similar populations have shown that high attrition rates are common among urban and ethnic minority adolescents with low SES (Seidman et al, 1994;Gonzales et al, 1996), and therefore also expected in our study. To minimize missing data, follow-up administrations were made one month after the initial administration to reach those students that were absent the first time.…”
Section: Limitationsmentioning
confidence: 37%
“…However, other longitudinal studies in similar populations have shown that high attrition rates are common among urban and ethnic minority adolescents with low SES (Seidman et al, 1994;Gonzales et al, 1996), and therefore also expected in our study. To minimize missing data, follow-up administrations were made one month after the initial administration to reach those students that were absent the first time.…”
Section: Limitationsmentioning
confidence: 37%
“…It also is noteworthy that we found support for the protective influence of traditional cultural values with a sample of 7 th grade students interviewed in the year following transition to middle school. Accumulating research indicates the transition to middle / junior high school represents a key turning point or "risky" transition for poor, inner-city adolescents (Roderick, 1995;Seidman, Allen, Aber, Mitchell,,& Feinman, 1994). School engagement and psychological well-being have been found to decline in the year following this transition (e.g., Eccles, Lord, & Midgley, 1991) and these declines are most pronounced and are more likely to lead to school dropout and externalizing behavior for minority youth attending schools in low-income, urban neighborhoods (Seidman, Lambert & Allen, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Gutman and Midgley (2000) found that African American early adolescents living in poverty experienced a significant decline in grade point average from fifth to sixth grade. In another study of poor minority youth, Seidman, Allen, Aber, Mitchell, and Fienman (1994) found that self-esteem, class preparation, and grade point average also declined significantly after the middle school transition (Seidman et al, 1994). Moreover, although African American students begin school with test scores that are similar to their European American peers, by middle school, many African American students have fallen two-grade levels behind (Steele, 1992).…”
Section: Multiple Risks Facing African American Youthmentioning
confidence: 99%